2001
DOI: 10.1074/jbc.m006492200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Regulation of Skeletal Cell Apoptosis

Abstract: Previously, we noted that inorganic phosphate (P i ), a major component of bone extracellular matrix, induced osteoblast apoptosis (Meleti, Z., Shapiro, I. M., and Adams, C. S. (2000 Bone adapts to mechanical and physiological stress by a unique form of tissue replacement contained within discrete structures defined as basic multicellular units (2). Within each of these units, the actual process of bone removal is carried out by osteoclasts; replacement bone matrix is synthesized and mineralized by cells of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
136
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(156 citation statements)
references
References 33 publications
13
136
4
1
Order By: Relevance
“…In addition to the regulation of growth factor bioavailability by MMPs, ECM remodeling also induces variations in calcium and phosphate ion concentrations. Interestingly, Adams and coworkers [58] demonstrated that, depending upon their extracellular concentrations, these ions could also regulate chondrocyte and osteoblast apoptosis. Thus, growth factors and ions might be involved in closely related molecular pathways that govern the equilibrium between survival and apoptosis of skeletal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the regulation of growth factor bioavailability by MMPs, ECM remodeling also induces variations in calcium and phosphate ion concentrations. Interestingly, Adams and coworkers [58] demonstrated that, depending upon their extracellular concentrations, these ions could also regulate chondrocyte and osteoblast apoptosis. Thus, growth factors and ions might be involved in closely related molecular pathways that govern the equilibrium between survival and apoptosis of skeletal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with fetuin-A gene-ablated mice showed an irregularity of bone mineralization that reinforced the role of fetuin-A in this process. [6,30] Moreover, in patients with end-stage renal failure with fetuin-A deficiency, decreased concentrations of Ca and P against increased osteoblast apoptosis have been suggested to have a negative effect on bone structure. [6] A study by Binkert et al [21] showed that in bone marrow cultures of rats treated with a high dose of dexamethasone, fetuin-A and TNF-β suppressed bone alkaline phosphatase, osteopontin, type I collagen, and bone sialoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Studies have also shown that fetuin-A can inhibit transforming growth factor beta (TGF-β)/bone morphogenic protein (BMP) activity. [6] In the absence of fetuin-A, inhibition of TGF-β/BMP occurs, and osteogenesis is subsequently stimulated. [7] Thus, the decrease in fetuin-A serum levels with respect to the metabolism of bone through osteoblast apoptosis and the TGF-β/BMP system can lead to osteo-inductive effects.…”
mentioning
confidence: 99%
“…Metals exhibit susceptibility to corrosion, poor osseointegration, and stress shielding [2,5]. Ceramics tend to be brittle, present low mechanical strength (in a porous configuration), and unpredictable in vivo degradation/dissolution rates [1,2,6,7]. Polymers on the other hand show reduced osseointegration capabilities, decreased cell-material interactions due to surface hydrophobicity, and excessive ductility for hard tissue replacement applications [1,2,8].…”
Section: Introductionmentioning
confidence: 99%